2023
DOI: 10.3389/fgene.2022.1097543
|View full text |Cite
|
Sign up to set email alerts
|

Functional gene polymorphisms and expression alteration of selected microRNAs and the risk of various gastric lesions in Helicobacter pylori-related gastric diseases

Abstract: Background:Helicobacter pylori (Hp) persistent infection is an important pathogenic factor for a series of chronic gastric diseases from chronic gastritis to gastric cancer. Genetic and epigenetic abnormalities of microRNAs may play a vital role in the pathological evolution of gastric mucosa in Helicobacter pylori-related gastric diseases (HPGD). This study aimed to investigate the relationship between miR-146a, miR-196a2, miR-149, miR-499 and miR-27a gene single nucleotide polymorphisms (SNPs) and their expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The authors demonstrated that the C allele of the mRNA-499 rs3746444 T>C SNP increased susceptibility to GC. Several other SNPs-miR-196a2 rs11614913, miR-27a rs895819, miR-499 rs3746444, miR-27a rs895819, miR-4427 rs701213, miR-548j rs4822739, miR-938 rs12416605, miR-4274 rs1553867776, miR-3175 rs1439619, miR-6891 rs6149511, miR-8084 rs404337, miR-4719 rs7500280 and miR-34b/c rs4938723-have been associated with an increased or decreased susceptibility to GC [58][59][60][61][62]. Interestingly, SNPs have been combined with other parameters to evaluate the correlation with gastric malignancy.…”
Section: Non-coding Rna In Gastric Cancer-their Role As Biomarkers An...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that the C allele of the mRNA-499 rs3746444 T>C SNP increased susceptibility to GC. Several other SNPs-miR-196a2 rs11614913, miR-27a rs895819, miR-499 rs3746444, miR-27a rs895819, miR-4427 rs701213, miR-548j rs4822739, miR-938 rs12416605, miR-4274 rs1553867776, miR-3175 rs1439619, miR-6891 rs6149511, miR-8084 rs404337, miR-4719 rs7500280 and miR-34b/c rs4938723-have been associated with an increased or decreased susceptibility to GC [58][59][60][61][62]. Interestingly, SNPs have been combined with other parameters to evaluate the correlation with gastric malignancy.…”
Section: Non-coding Rna In Gastric Cancer-their Role As Biomarkers An...mentioning
confidence: 99%
“…Interestingly, SNPs have been combined with other parameters to evaluate the correlation with gastric malignancy. Interestingly, the combination of the miR-196a2 rs11614913 polymorphism and H. pylori seems to be associated with gastric precancerous lesions [58].…”
Section: Non-coding Rna In Gastric Cancer-their Role As Biomarkers An...mentioning
confidence: 99%